Optically amplified WDM networks - Zyskind, John (Elsevier/Academic Press, 2011)
"The book provides an overview of optical amplifiers and reconfigurable networks before examining in greater detail the issues of importance to network operators and equipment manufacturers, including 40G and 100G transmission. Optical amplifier design is fully considered, focusing on fundamentals, design solutions and amplifier performance limitations. Finally, the book discusses other emerging applications for optical amplifiers such as optical networks for high data rate systems, free space systems, long single span links and optical digital networks"--Provided by publisher.